Śṟī Patmanābhasvāmi Kṣētṟaṃ, Tiruvanantapuraṃ : aitihyavuṃ caritṟavuṃ (Śṟī Patmanābhasvāmi Kṣētṟaṃ Eksikyūṭṭīvȧ Āphīsar, 1977)
On the history and legend of Sree Padmanabha Swamy Temple (Trivandrum, India)